PENGARUH MOTIVASI, KEMAMPUAN MANAJERIAL KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU DI SEKOLAH MENENGAH KEJURUAN ( SMK ) YPT PANGKALAN BERANDAN KABUPATEN LANGKAT - Agus Salim (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The formulation in this research is how the influence of motivation, school head and the organizational climate simultaneously to the performance of teachers in vocational high School (SMK) YPT Pangkalan Berandan District, and the purpose of this research is To know and analyze the influence of motivation, school head and climate of the organization simultaneously to the performance of teachers in vocational high School (SMK) YPT Pangkalan Berandan and Langkat district.This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, questionaire questions and documentation studies. Sample in this study as many as 44 teachers in vocational high School (SMK) YPT Pangkalan Berandan and Langkat district. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The results of the test in unison showed that the principal motivation and managerial ability of the school as well as the organizational climate has a significant effect on the performance of Vocational High School (SMK) YPT basis, and the value of coefficient of determination of 0.840 or 84.0%. Partially, motivation (X1) has a positive and significant effect on the performance of Vocational secondary school (SMK) YPT, and with a regression coefficient value of 0452 or 45.2%. The principal's managerial ability (X2) has a positive and significant impact on the performance of Vocational secondary school (SMK) YPT Berandan and with a regression coefficient value of 0407 or 40.7%. Climate Organization (X3) positively and significantly affect the performance of vocational secondary school (SMK) YPT, and with a regression coefficient value of 0197 or 19.7%. The highest value of a regression coefficient is the master motivation of 0452 or 45.2%.